The way Hollywood tells it : story and style in modern movies - Bordwell, David (Berkeley : University of California Press, 2006)
Includes information on Woody Allen, Robert Altman, Asian films, Brian de Plama, European cinema, Alfred Hitchcock, Hong Kong films, Sam Peckinpah, Arthur Penn, Otto Preminger, Brett Ratner, Martin Scorsese, Steven Spielberg, Oliver Stone, Orson Welles, American Graffiti, At Long Last Love, A Beautiful Mind, Bonnie and Clyde, Chinatown, Citizen Kane, The Godfather, Jaws, Jerry Maguire, Lord of the Rings trilogy, Matrix trilogy, Memento, Raiders of the Lost Ark, Sixth Sense, Star Wars series, Two Weeks Notice, arcing shots, axis of action, black and white footage, camera movement, characterization, climax, close ups, comedies, complicating action, cutting, dialogue hook, directors, editing, energy, epilogue, establishing shots, fantasy, film noir, flashbacks, following shots, foreshadowing, four part structure, framing, handheld shots, heroes, horror, hyperclassical construction, independent films, innovation, intensified continuity, intercutting, long lens, long takes, low budget films, montage sequences, motifs, multiple camera shooting, narrative, over the shoulder shots, overt narration, plot, postclassical cinema, protagonists, puzzle films, rapid cutting, reverse order plotting, romantic comedy, science fiction, set up, shots, singles, soundtracks, special effects, Stedicam, story development, studio era, television, thrillers, time, tracking shots, video, violence, visceral effects, visual style, wide angle lens, wide screen, wipe by cuts, wipes, etc.
A real story ; Continuing tradition, by any means necessary ; Pushing the premises ; Subjective stories and network narratives ; A certain amount of plot: tentpoles, locomotives, blockbusters, megapictures, and the action movie -- A stylish style ; Intensified continuity: four dimensions ; Some likely sources ; Style, plain and fancy ; What's missing?
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Motion pictures -- United States -- History; Motion picture industry -- United States -- History; Motion pictures -- Aesthetics; Cinéma -- États-Unis -- Histoire; Cinéma -- Esthétique.; Cinéma -- Industrie -- États-Unis -- Histoire; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- General; Motion picture industry; Motion pictures; Motion pictures -- Aesthetics; United States; american art; american culture; american film; american history; american life; artistic; blockbusters; cinema studies; cinematic; cultural history; cultural studies; film history; film studies; filmmaker; filmmaking; hollywood; indie cinema; indie movies; movie director; movie editing; movie genres; movie studio; moviemakers; moviemaking; romantic comedies; social history; social studies; storytelling; visual arts; Motion pictures; History; Motion pictures; Films